Oil exploration and production in Sub-Saharan Africa, 1990-present: Trends and developments. Issue 2 (April 2019) - Graham, Emmanuel; Ovadia, Jesse Salah
Highlights: African states have enacted legal regimes for the petroleum industry and for local content that can be analyzed from a regional perspective. While there has been an expansion of upstream oil and gas activities across Sub-Saharan Africa. Despite the expansion, a general weakness remains in legal and institutional frameworks for petroleum management. Prospects for petro-development may be waning due to new limits of the possible. Abstract: The exploration and production of oil and gas continue to be vigorously pursued by African states and international corporations—both large and small. However, with unpredictable fluctuations in oil prices it becomes more difficult to exploit these resources in ways which accrue net benefits to both the state and its citizens. The oil and gas industry in Africa continues to grow and attract new investment, especially from China and India. Despite the lower price of oil, exploration and production activities continue to be carried out. At the same time, the possibilities for oil and gas to be a blessing narrow. Natural resource-based development has always been a difficult objective for any state. The question now may be whether embracing oil and gas is socially responsible: as renewable energy becomes more cost-effective and societies transition into a post-carbon world, the prospects for African states to make good use of carbon resources are waning. In exploring the closing window for petro-development in Africa, this paper uses a comparative cross-regional analysis of trends and developments to highlight how weak legal frameworks and a lack of institutional capacity pose major challenges for the continent's states in managing their natural resources.